2019
DOI: 10.1115/1.4042298
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Redistribution in PC3 Tumors Induced by Local Heating in Magnetic Nanoparticle Hyperthermia: In Vivo Experimental Study

Abstract: In magnetic nanoparticle hyperthermia, a required thermal dosage for tumor destruction greatly depends on nanoparticle distribution in tumors. The objective of this study is to conduct in vivo experiments to evaluate whether local heating using magnetic nanoparticle hyperthermia changes nanoparticle concentration distribution in prostatic cancer (PC3) tumors. In vivo animal experiments were performed on grafted PC3 tumors implanted in mice to investigate whether local heating via exposing the tumor to an alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…S2, the FMT images of the multifunctional nanocarriers 1 h before (at t ¼ 24 h) and 1 h after (t ¼ 25 h) MNH treatment, indicates that the nano-heaters distribution probably changed during the treatment. Similar MNH experimental results in a PC3 tumor model using microCT images were recently reported [74]. The result suggests that the nano-heaters might diffuse during MNH.…”
Section: Limitations Of the Methodology And Final Considerationssupporting
confidence: 88%
“…S2, the FMT images of the multifunctional nanocarriers 1 h before (at t ¼ 24 h) and 1 h after (t ¼ 25 h) MNH treatment, indicates that the nano-heaters distribution probably changed during the treatment. Similar MNH experimental results in a PC3 tumor model using microCT images were recently reported [74]. The result suggests that the nano-heaters might diffuse during MNH.…”
Section: Limitations Of the Methodology And Final Considerationssupporting
confidence: 88%
“…PC3 xenograft tumors were implanted in 14 Balb/c Nu/Nu male mice (28-32 g, The Jackson Lab, Bar Harbor, ME), with one tumor in each mouse, similar to our previous experiments [19][20][21]. A PC3 cell solution containing 5*10 6 cells was injected into the left flank of the mouse using a 27-gauge needle (Tuberculin Syringe w/Needle by BD, Fischer Scientific, Springfield, NJ).…”
Section: Tumor Implantation and In Vivo Animal Experimentsmentioning
confidence: 99%
“…Recently, microCT imaging techniques have been proposed as a non-invasive and non-destructive method for investigating nanoparticle distribution in tumors. Although microCT does not allow direct visualization of individual nanoparticles, the accumulation of nanoparticles in tissue would result in a region with a much higher density than the rest of the tissue, thus, the density variations can be detected by a microCT system [19][20][21]. Several recent studies [19][20][21] have shown the feasibility of imaging and quantifying detailed 3-D nanoparticle distribution in both gels and tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the small size of MNPs also boosts the risk of the in vivo redistribution, incurred by the release of dead cell intracellular solution and the enhancement of vascular permeability after hyperthermia once [1,2], spreading to the peripheral healthy tissue and lowering curative effect [3][4][5]. For instance, in the treatment of human prostate cancer on the mouse back, the 25 min hyperthermia resulted in the Fe 3 O 4 MNPs spreading from the intratumoral injection site to tumor periphery [2]. In the treatment of glioma in the rat thalamus, the dextran-coated Fe 3 O 4 MNPs were also found to spread into the surrounding tissue shortly after intratumoral injection [3].…”
Section: Introductionmentioning
confidence: 99%